Multiple stellar populations in Magellanic Cloud clusters – V. The split main sequence of the young cluster NGC 1866. Issue 4 (17th November 2016) - Milone, A. P.; Marino, A. F.; D'Antona, F.; Bedin, L. R.; Piotto, G.; Jerjen, H.; Anderson, J.; Dotter, A.; Criscienzo, M. Di; Lagioia, E. P.
Abstract: One of the most unexpected results in the field of stellar populations of the last few years is the discovery that some Magellanic Cloud globular clusters younger than ∼400 Myr exhibit bimodal main sequences (MSs) in their colour–magnitude diagrams (CMDs). Moreover, these young clusters host an extended main-sequence turn-off (eMSTO) in close analogy with what is observed in most ∼1–2 Gyr old clusters of both Magellanic Clouds. We use high-precision Hubble Space Telescope photometry to study the young star cluster NGC 1866 in the Large Magellanic Cloud. We discover an eMSTO and a split MS. The analysis of the CMD reveals that (i) the blue MS is the less populous one, hosting about one-third of the total number of MS stars; (ii) red MS stars are more centrally concentrated than blue MS stars; (iii) the fraction of blue MS stars with respect to the total number of MS stars drops by a factor of ∼2 in the upper MS with m F 814 W ≲ 19.7. The comparison between the observed CMDs and stellar models reveals that the observations are consistent with ∼200 Myr old highly rotating stars on the red MS, with rotation close to critical value, plus a non-rotating stellar population spanning an age interval between ∼140 and 220 Myr, on the blue MS. Noticeable, neither stellar populations with different ages only, nor coeval stellar models with different rotation rates, properly reproduce the observed split MS and eMSTO. We discuss these results in the context of the eMSTO and multiple MS phenomenon.